[The German Network of University Medicine: technical and organizational approaches for research data platforms]. - Heyder, Ralf; Kroemer, Heyo K.; Wiedmann, Silke; Pley, Christina; Heyer, Carolin; Heuschmann, Peter; Vehreschild, Jörg Janne; Krefting, Dagmar; Illig, Thomas; Nauck, Matthias; Schaller, Jens; Kraus, Monika; et al. (Bundesgesundheitsblatt, Gesundheitsforschung, Gesundheitsschutz, 2023)
The Network University Medicine (NUM) consists of 36 university clinics in Germany. It was set up to coordinate COVID-19 university medicine research activities on a national level. This required, among other things, common infrastructures for the collection, storage, and use of medical research data. These infrastructures were not available in the required form when the NUM started in April 2020. Medical research data are extremely heterogeneous and reach far beyond "real world data" from patient care. There was no "one size fits all" solution, so NUM built five infrastructures for different types of data, different ways of obtaining data, and different data origination settings. To prevent the creation of new data silos, all five infrastructures operate based on FAIR principles (findable, accessible, interoperable, reusable). In addition, NUM is implementing an overarching governance framework to manage the evolution of these five infrastructures. The article describes the current state of development and possible perspectives with a strong focus on technical and organizational aspects.
EVALuna2:544914